2019
DOI: 10.1097/aog.0000000000003452
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Etonogestrel Concentrations and Bleeding Patterns in Contraceptive Implant Users

Abstract: OBJECTIVE: To estimate whether serum etonogestrel concentrations influence bleeding patterns and related side effects in contraceptive implant users. METHODS: We conducted a prospective cross-sectional study with healthy, reproductive-aged women using etonogestrel implants for 12–36 months. Participants completed a brief questionnaire to assess their current bleeding pattern and any experience of abnormal bleeding with the implant. We then measured seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 15 publications
1
29
0
Order By: Relevance
“…Mifepristone combined with either E2 or doxycycline was significantly more effective than placebo in stopping bleeding in women with prolonged and/or frequent bleeding during Implanon use [67,68]. In a prospective cross-sectional study, Lazorwitz et al [66] studied 350 healthy, reproductive-aged women using ENG implants for 12-36 months, showing that 20% received a prescription for OCs [69]. In a prospective randomized study [70], 84 Implanon users with prolonged or frequent bleeding were assigned to receive OCs containing Ethinlestradiol (EE2) 20 mcg/150 mg DSG for two cycles.…”
Section: Implanonmentioning
confidence: 99%
“…Mifepristone combined with either E2 or doxycycline was significantly more effective than placebo in stopping bleeding in women with prolonged and/or frequent bleeding during Implanon use [67,68]. In a prospective cross-sectional study, Lazorwitz et al [66] studied 350 healthy, reproductive-aged women using ENG implants for 12-36 months, showing that 20% received a prescription for OCs [69]. In a prospective randomized study [70], 84 Implanon users with prolonged or frequent bleeding were assigned to receive OCs containing Ethinlestradiol (EE2) 20 mcg/150 mg DSG for two cycles.…”
Section: Implanonmentioning
confidence: 99%
“…This was a secondary analysis of a parent pharmacogenomic association study 13 . The methodology for study enrollment has been previously published, including all inclusion and exclusion criteria, assessment of bleeding side effect profiles and subjective weight gain, and measurement of etonogestrel concentrations 4,6,13 . All participants in the parent study were users of the etonogestrel contraceptive implant and had used their implant between 12 and 36 months at the time of enrollment 13 .…”
Section: Methodsmentioning
confidence: 99%
“…These progestin‐related side effects are the most commonly reported reasons for early contraceptive method discontinuation, which places patients at increased risk of unintended pregnancies and related adverse health and social outcomes 1 . From our own work, we found that participants who self‐reported their race as Black or African American were more likely to report a monthly period during contraceptive implant use (adjusted odds ratio [aOR] 2.22, 95% confidence interval [CI] 1.14–4.32) and that women of self‐reported Asian or Pacific Islander race were more likely to report amenorrhea (aOR 3.25, 95% CI 1.15–9.22) as compared with all other participants 4 . These associations are not solely found with bleeding side effects, as we also found that self‐reported Hispanic or Latina participants had almost three times the odds of reporting subjective weight gain during contraceptive implant use 6 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations